Diskon ke Checkout: Pengaruh Promo dan Live Streaming Shopee Terhadap Keputusan Pembelian Produk Fashion - Ulayya, Jihan; Bayangkara, Agasta Veda; Ramawati, Diah Bintang; Lintang, Queendira; Damayanti, Citra; Isnaini, Mufidah (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
The purpose of this study was to see how promotions and live streaming features impact the decision of Shopee users to purchase fashion products in the 2022 intake. This quantitative study involved 54 respondents from a population of 117 students selected through a simple random sampling method. Primary data were collected through online questionnaires and analyzed using multiple regression using SPSS. Validity, reliability, classical assumptions, and hypothesis tests were also conducted. The study shows that students of Economics Education, Sebelas Maret University, 2022 intake significantly choose fashion products because of promotions and Shopee's live streaming features. Promos are considered to be able to save consumer spending, thus increasing interest and enthusiasm for transacting through the Shopee application. Meanwhile, the live streaming feature makes it easier for consumers to see products directly, assess quality, and make purchases more practically. As for further researchers, it is recommended to add other variables (for example, consumer trust), compare with other e-commerce platforms, use mixed methods, analyze different user segments, and examine the long-term impact on brand loyalty.